2010
DOI: 10.1016/j.ajog.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between levator ani muscle injuries on magnetic resonance imaging and fecal incontinence, pelvic organ prolapse, and urinary incontinence in primiparous women

Abstract: Objective-To correlate the presence of major levator ani muscle (LAM) injuries on magnetic resonance imaging (MRI) with fecal incontinence (FI), pelvic organ prolapse (POP) and urinary incontinence (UI) in primiparous women 6-12 months postpartum.Study design-A published scoring system was used to characterize LAM injuries on MRI dichotomously (MRI−, no/mild versus MRI+, major).Results-Major LAM injuries were observed in 17/89(19.1%) women who delivered vaginally with external anal sphincter (EAS) injuries, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
2
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 22 publications
9
83
2
7
Order By: Relevance
“…45 Our findings on objective assessment are in accordance with the literature, where POP, enlarged hiatus and LAM avulsion are inter-related. 5,6,10,14,16,46 In contrast to another study performed postpartum, 18 we found that women both with and without major LAM avulsion had significantly more faecal incontinence, without differences between groups. As shown previously we expected women with major avulsions to report more faecal incontinence, as the incidence of OASIS was higher (n = 8/30) (K. W. M. Van Delft, R. Thakar, A. H. Sultan, N. Schwertner-Tiepelmann, K. B. Kluivers [accepted].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…45 Our findings on objective assessment are in accordance with the literature, where POP, enlarged hiatus and LAM avulsion are inter-related. 5,6,10,14,16,46 In contrast to another study performed postpartum, 18 we found that women both with and without major LAM avulsion had significantly more faecal incontinence, without differences between groups. As shown previously we expected women with major avulsions to report more faecal incontinence, as the incidence of OASIS was higher (n = 8/30) (K. W. M. Van Delft, R. Thakar, A. H. Sultan, N. Schwertner-Tiepelmann, K. B. Kluivers [accepted].…”
Section: Discussioncontrasting
confidence: 99%
“…An increase of PFMS during pregnancy, followed by a reduction in strength postpartum, has been described previously. 42 Although worsening of POP following vaginal delivery has been demonstrated previously in prospective studies, 18,41,43 this was not related to LAM avulsion. Our study revealed more anterior compartment prolapse for women with LAM avulsion.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Determining the presence of atrophy can help predict the success of sphincter defect repair in patients being considered for surgery [60]. Concurrent abnormalities of the levator ani muscle complex are also demonstrated on MRI [61,62].…”
Section: Anal Incontinencementioning
confidence: 99%
“…Larger genital hiatus and a greater fixed and dynamic perineal descent are seen in patients with abnormal levator muscle [79,80]. In addition, major muscle loss can be seen in combination with external anal sphincter injury on MRI in postpartum patients [61]. In patients with recurrent POP after surgery, major levator muscle defects may be a contributing factor [81][82][83][84].…”
Section: Pelvic Floor Integritymentioning
confidence: 99%